Influência da perfuração da membrana sinusal na formação de osso vital, no desenvolvimento de sinusite maxilar e na taxa de sobrevivência de implantes instalados na maxila: análise histomorfométrica - Ornelas, Ana Carla Fabricio [UNESP] (2014)
Reports showed abandon of the procedure for sinus lifting to detect a perforation because the prognosis of implant exposure to the sinus cavity is difficult to predict. The objective was evaluate the influence of sinus membrane perforation in the integration of dental implants installed in the maxillary sinus of rabbits after sinus lifting or through the same by BIC and BA. Twenty dental implants were installed in the maxillary sinus after the elevation of the sinus lifting (n = 10) or membrane perforation (n = 10). Euthanasia was performed at 7 and 40 days. Comparing the BIC intra-group in different periods, the values were statistically significant for MI and MP (p < 0,05). For BA at 40 days values for MP and MI (p < 0.05) as compared within the same group in different periods, values for BA MI (p < 0.05), but the same was not observed for MP . It was concluded that the membrane perforation interfere with the process of osseointegration of implants, however, is not compromised in order to contraindicate procedure